Pembatalan Perkawinan Yang Disebabkan Salah Sangka Mengenai Diri Suami - Kastella, Lia Syarifah (Universitas Islam Sumatera Utara, 2024)
The annulment of a marriage due to misrepresentation of the husband is an important issue in Islamic law, given that honesty and transparency are the main foundations of the marriage relationship. This article discusses the legal basis underlying annulment of marriage due to misrepresentation, including aspects of identity, status, and important conditions that should have been known prior to marriage. The legal procedure for filing an annulment in a religious court is also discussed, emphasizing the importance of evidence and testimony in the process. In addition, the article highlights the ethical and moral values contained in Islamic teachings, which require both parties to be honest and open. The conclusion suggests that marriage annulment in this context is a legitimate measure to protect the rights and dignity of individuals, as well as ensuring justice in the institution of marriage.Keywords: Marriage annulment, misrepresentation